2018
DOI: 10.1590/0103-8478cr20170480
|View full text |Cite
|
Sign up to set email alerts
|

Felis catus gammaherpesvirus 1 (FcaGHV1) and coinfections with feline viral pathogens in domestic cats in Brazil

Abstract: Felis catus gammaherpesvirus 1 (FcaGHV1) may causes an asymptomatic infection that result in an efficient transmission and subsequently dissemination of the virus in feline population. This study used molecular detection by qPCR (quantitative PCR) based on DNA polymerase gene fragment amplification to evaluate the occurrence of FcaGHV1 and its correlation with other feline viral pathogens, such as Carnivore protoparvovirus 1 (CPPV-1), Felid alphaherpesvirus 1 (FeHV-1), and feline retroviruses such as feline im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 37 publications
7
24
1
Order By: Relevance
“…We did not find any statistically significant risk factors for LcaGHV1 infection (Table 3). We and others had previously found that being male and of older age were significant risk factors for FcaGHV1-positive status in domestic cats Troyer et al, 2014), and this relationship has been confirmed by other studies (Ertl et al, 2015;Kurissio et al, 2018;McLuckie et al, 2016;Stutzman-Rodriguez et al, 2016). This relationship between sex and infection status was not observed in wild felids (pumas and bobcats), however the association with higher age was .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We did not find any statistically significant risk factors for LcaGHV1 infection (Table 3). We and others had previously found that being male and of older age were significant risk factors for FcaGHV1-positive status in domestic cats Troyer et al, 2014), and this relationship has been confirmed by other studies (Ertl et al, 2015;Kurissio et al, 2018;McLuckie et al, 2016;Stutzman-Rodriguez et al, 2016). This relationship between sex and infection status was not observed in wild felids (pumas and bobcats), however the association with higher age was .…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, the branching pattern seen in the evolution of felids is nearly identical to that of their respective GHVs (Johnson et al, 2006), suggesting speciation could account for the observed felid percavirus subclade. More recently, FcaGHV1 has been identified in Europe (Ertl et al, 2015), Japan (Tateno et al, 2017), and Brazil (Kurissio et al, 2018), suggesting world-wide distribution. Though it is not clear whether this world-wide distribution is natural or whether it is due to human activity, especially since domestic cats are pets in many parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FcaGHV1 infection has been reported in cats from Australia, USA, UK, central Europe, Japan, Singapore and Brazil, with 9.6% to 23.6% testing positive for FcaGHV1 on whole blood quantitative real-time PCR (qPCR) [ 1 , 10 , 11 , 12 , 13 , 14 ]. One study showed that anti-FcaGHV1 antibodies identified persistent infection in 35% of cats, and the true infection prevalence may be higher [ 15 ].…”
mentioning
confidence: 99%